2019
DOI: 10.1371/journal.pone.0226199
|View full text |Cite
|
Sign up to set email alerts
|

New insights into intranuclear inclusions in thyroid carcinoma: Association with autophagy and with BRAFV600E mutation

Abstract: BackgroundIntranuclear inclusions (NI) in normal and neoplastic tissues have been known for years, representing one of the diagnostic criteria for papillary thyroid carcinoma (PTC). BRAF activation is involved among others in autophagy. NI in hepatocellular carcinoma contain autophagy-associated proteins. Our aim was to clarify if NI in thyroid carcinoma (TC) have a biological function.MethodsNI in 107 paraffin-embedded specimens of TC including all major subtypes were analyzed. We considered an inclusion as p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
11
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 56 publications
(77 reference statements)
4
11
0
3
Order By: Relevance
“…Hence, the 1/2 criteria had higher specificity in distinguishing PTC from FA than the 1/3 criteria, and applying either criterion would be useful in distinguishing FA from follicular variant papillary carcinoma. Therefore, we agree with Schwertheim et al (7) that p62 is a useful marker for NuIns. However, since NuIns have different sizes, shapes, and numbers, distinct criteria for evaluating NuIns are mandatory.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Hence, the 1/2 criteria had higher specificity in distinguishing PTC from FA than the 1/3 criteria, and applying either criterion would be useful in distinguishing FA from follicular variant papillary carcinoma. Therefore, we agree with Schwertheim et al (7) that p62 is a useful marker for NuIns. However, since NuIns have different sizes, shapes, and numbers, distinct criteria for evaluating NuIns are mandatory.…”
Section: Discussionsupporting
confidence: 93%
“…We designed this study based on previous reports that p62 accumulation is pathogenic. As Schwertheim et al (7) concluded that p62 expression in NuIns indicates their contribution to autophagy, we hypothesized that p62In cells may be created due to accumulation of p62 not eliminated by autophagy, and that they drive pathological changes in the thyroid tissue in PTC. When stimulated by growth factors, normal cells generally increase their glutamine and glucose uptake as energy sources.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lysosome proteases cathepsin B and D together with the presence of heterolysosomes in TEM are suggestive for an active proteolytic activity in type1 NI. This proteolytic activity could also explain the nearby degenerated cell organelles, which we and others have observed in NI 20,21,33,34 . This hypothesis is supported by the identification of autophagy related proteins such as LC3B, p62, ubiquitin and cathepsins in NI.…”
Section: Discussionsupporting
confidence: 64%
“…In NAFLD, nuclear vacuolation is linked to aging process or senescence but no differentiation is made between NI with or without a limiting membrane 19 . Our recent study of membrane-bounded NI in HCC 20 and in thyroid carcinomas 21 has shown the presence of autophagy-associated proteins and proteases within the inclusions; in HCC the occurrence of inclusions was associated with patients' survival benefit 20 . Jaskolski et al described that autophagy is involved in the pathogenesis of intranuclear vacuolation in meningeomas 22 ; their electron microscopic studies revealed lysosomal bodies and autophagic vacuoles within these NI, suggesting an active macroautophagy process 22 .…”
mentioning
confidence: 99%